2008
DOI: 10.1152/ajpcell.00355.2007
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of skeletal muscle mass after extensive injury: positive effects of increased contractile activity

Abstract: Richard-Bulteau H, Serrurier B, Crassous B, Banzet S, Peinnequin A, Bigard X, Koulmann N. Recovery of skeletal muscle mass after extensive injury: positive effects of increased contractile activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…The choice of BaCl 2 among myotoxins was based on its low cost and easy accessibility. BaCl 2 induces muscle fiber necrosis while completely preserving the basement membrane (4), and the subsequent muscle regeneration follows a process and timeline comparable to those induced by snake venoms or freezing (10,14,20,21,25,33). Ten-week-old male mice were used in all the regeneration experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The choice of BaCl 2 among myotoxins was based on its low cost and easy accessibility. BaCl 2 induces muscle fiber necrosis while completely preserving the basement membrane (4), and the subsequent muscle regeneration follows a process and timeline comparable to those induced by snake venoms or freezing (10,14,20,21,25,33). Ten-week-old male mice were used in all the regeneration experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have investigated the role of exercise/contractile activity after skeletal muscle injury. It appears that exercise (running) increases skeletal muscle mass and the cross-sectional area of regenerating muscle as well as the recovery of metabolic properties (171,279). These effects can be explained by a higher activation of the mTOR pathway, the master regulator of cell growth and protein synthesis previously described as a redox-regulated molecule (294) and of PGC-1a (171), the master regulator of oxidative metabolism (191,196).…”
Section: A Exercise As Therapymentioning
confidence: 99%
“…TUNEL-positive myofiber nuclei (arrow) were located in the subsarcolemma, but central nuclei were not detected. Bar 50 lm [40]. Interestingly, Asakura et al [8] have demonstrated that MyoD regulates not only differentiation and proliferation of satellite cells but also the apoptosis response during the regenerating phase.…”
Section: Myofiber Apoptosis During the Inflammation Phasementioning
confidence: 99%